The Influence of the Role of the School Principal on the Performance of East Lembean District Junior High School Teachers - Lompoliu, Evelien; Supit, Michella Christy Tania (International Journal of Information Technology and Education, 2023)
The background to this research is the reality that shows the low performance of junior high school teachers in East Lembean District. The role of the school principal is a factor that influences low teacher performance. This research uses a quantitative research approach and an ex post facto type of research. The research population was all elementary school teachers in East Lembean District, Minahasa Regency, totaling 75 teachers. The number of research samples is the same as the population. The analysis of this research includes normality test analysis, homogeneity test, linearity test, and multicollinearity test. Hypothesis tests include correlation tests, ANOVA tests, summary tests, and regression coefficient tests. The research results show that there is a positive influence of the role of the principal on teacher performance at 34.6%. Coaching is needed to improve the role of school principals so that teacher performance also increases.